The Principal Leadership Style in Developing Discipline Character - Brata, Diah Puji Nali; Mahatmaharti, Agung Kesna; Wajdi, Muh Barid Nizarudin (International Journal of Psychosocial Rehabilitation, 2020)
The student’s character building in Vocational High School (SMK) is the character conformity learners with employment practices learners, one character discipline. Habituation character of discipline in schools is expected to emerge both characters more in self-learners. The principal’s leadership style is the key to success in implementing character education. This study aims to describe the form of character development discipline, leadership style in character development disciplines, and its effects on the 1st Jombang Vocational High School. The research approach is qualitative descriptive with a case study design. Examination of the data validity used triangulation of sources and methods. The results show that the shape of the character development of the discipline in the school is a process of internalization and socialization through habituation and conduciveness atmosphere creation inside and outside the classroom. Habituation through the obligation for new learners to follow the discipline of education in cooperation with the Republic Indonesia Air Force in Kabuh, Jombang region, conduciveness atmosphere creation through a commitment to comply with the order on time within and outside of learning that applies to students and teachers. Schools evaluate how the results reflect the teacher’s and students disciplined behaviors, there are a reward and punishment, and efforts to improve discipline behavior. The principal leadership style in developing the discipline character is transformational leadership as headmaster is committed to transform the character value for each member of the school community, for example, motivating the development, participatory decision making, improve collaboration, and mutual have high confidence in achieving success character development disciplines. The character development impact is school discipline can maintain relations of caring, respect, support, and collaboration between members of school staff, teachers, and learners. The school has academic and behavioral high levels and provides support for the discipline code development. Learners consider the rules as clear, fair, and not too loud. As a result of the intensive and collaborative evaluation, there were positive changes in the school about a late entry at school.